Sensitivity Analysis on Soil and Water Assesment Tool (SWAT) Model at Brantas Watershed, East Java Indonesia - Mohamad Wawan Sujarwo; Indarto Indarto; Marga Mandala (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2022)
Brantas Watershed and its tributaries (approximately 14,103 km2) are essential in supplying water for About 30% of the East Java province population. Management of water resources in this watershed has become a challenging issue. The modelling processes' conformity and results to mimic the existing hydrological processes are still in question. This study aims to analyze sensitive parameters of the SWAT (Soil & Water Assessment Tool) model on the significant watershed. The input model is climate and spatial (DEM, soil layer, LULC) data. The observes the hydrological processes monthly and annually from the model result. Next, Sensitivity analysis using the SWAT-CUP tool and SUFI algorithm shows 18 sensitive parameters. The nine (9) parameters have a more than 50% sensitivity level. The four (4) correlated to the soil layer's runoff generation and water movement. Then, eight (8) parameters are related to baseflow calculation. Simulation results illustrate the strong effect of climate change (especially rainfall) on water yield and sedimentation.